True fertilisation failure in captivity is rare - Ashleigh F. Marshall; François Balloux; Liz Brown; Edmund Flach; Anne Richardson; Tammy E. Steeves; Simon Spiro; Gary Ward; Nicola Hemmings; Patricia Brekke (Global Ecology and Conservation)
Species recovery through captive breeding can be hindered by low reproductive success. However, we know little about the drivers of early reproductive failure in captive populations, due to difficulties distinguishing fertilisation failure from early embryo mortality in most animals. Here, we apply advanced fertility diagnostics on unhatched eggs from 30 avian captive-breeding programs, to assess true rates of fertilisation failure. We find that fertilisation failure is rare across all species, and the main driver of early reproductive failure is early embryo mortality. We also find that macroscopic examination of undeveloped eggs inflates estimates of fertilisation failure rates in breeding programmes. Finally, we find no evidence that fertilisation failure rates are higher in threatened than non-threatened captive birds, providing hope that with careful management, hatching outcomes may be improved in threatened captive populations. Our results show that accurate fertility diagnosis in managed oviparous species provides crucial information on individual reproductive potential, helping the design of more appropriate management interventions to improve recovery.